Effect of plastic pyrolysis oil and its blends with diesel on Cetane Index - Karn, Rupesh Lal; Aryal, Suman; Neupane, Barsha `; Bhattarai, Kushal; Palikhel, Laxman (Journal of Innovations in Engineering Education, 2021)
Availability and higher gasoline price have attracted the attention of researchers towards alternative fuels. Plastic is produced from the byproduct of gasoline products, which possesses a higher possibility of recycling the waste plastic as an alternative fuel. Research conducted on plastic fuel shows that a diesel engine can run with 100% plastic oil. The present work is focused on the effect of distilled plastic oil on the cetane index as the cetane index is a major fuel property of diesel that affects the ignition quality and exhaust emissions of the engine. For the measurement of the cetane index, two standards are followed and they are ASTM D4737 and ASTM D976. It is found that Crude plastic oil produced from thermal pyrolysis of waste plastic possesses a wide variety of hydrocarbon i.e. lower to higher hydrocarbon. From the fractional distillation of crude plastic oil at three temperature ranges 200◦C, 290◦C and up to the final boiling point, it gave petrol grade oil and diesel grade oil (both low and high grade). Also, it was found that the recovery of distilled high-grade plastic oil is higher than other distilled crude plastic oil. Along with this, crude plastic oil, as well as high-grade plastic oil, have a higher cetane index than the diesel available in the market. Similarly, blending diesel with high-grade plastic oil up to 20% by volume and with low-grade plastic oil up to 10% by volume increases the cetane index of fuel.